PENGAWASAN LIMBAH INDUSTRI PERUSAHAAN KELAPA SAWIT DI KABUPATEN PELALAWAN - ", Mulyani; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Plantation sector, especially oil palm and rubber make a significant contribution to the economy Palalawan, oil palm plantations are in all districts in Pelalawan with oil palm acreage in 2014 was recorded 118,262.02 ha. However, oil palm companies also have a negative impact on the environment if not properly supervised dikeola to the maximum. One of the negative impact that the environmental pollution caused by waste oil palm production. This study aims to determine the synergy describe supervision, develop surveillance, discovered the concept of supervision of industrial waste in Pelalawan.This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. Supervision conducted by the Environment Agency on industrial waste in Pelalawan attached and bound, so there is a schedule of visits and sanctions for violations. Besides monitoring can also be administered by LSM and community to provide a better comparison of results again in industrial waste management. However, the lack of synergy between the government and society in monitoring industrial waste. Obstacles encountered in monitoring industrial waste that internal factors (lack of personnel, facilities and infrastructure support) and external factors that limited companies and testing laboratories wastes very few in number.Keywords: Implementation, Monitoring, Synergy, Industrial Waste